Ratio Decidendi Decision No 1/Pdt.GS/2018/PN.Mjn Against Breach in Agreement - kartika, eka dewi; Rais, M. Tasbir (Kirana Publisher (KNPub), 2023)
In the case of case decision No 1/Pdt.GS/2018/PN.Mjn, The case arose when the two parties entered into an agreement in September 2015. That the creditor did not pay the loan installments in accordance with what was agreed in the acknowledgment of debt since September 2015. Due to the position of the debtor on a non-performing loan, the creditor filed a default lawsuit to court on the basis of a letter of action. Debt Acknowledgment. Ratio decidendi The decision of the Majene District Court Number 1/PdtG.S/2018/Pn.Mjn decided that the debtor as the defendant had defaulted on the object of the claim for acknowledgment of debt. The letter of acknowledgment of debt is a Grosse Deed, not an agreement, while an agreement is an object of default. The execution of the acknowledgment of debt is carried out through the court by means of a request for execution not a lawsuit, so that the lawsuit filed is blurred in the case.